2017
DOI: 10.18203/2320-6012.ijrms20170149
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based eye health survey to see the pattern of eye diseases in Uttarakhand, India

Abstract: Background: The cause of blindness and low vision differs in different countries and communities. The requirements of eye services also vary according to the need of the native population. Studies showing the pattern of ocular morbidity are needed to build better infrastructure of eye care facilities.Methods: This prospective study was conducted in eye department of Government Doon Medical College, Dehradun, Uttarakhand, India between April 2016 to May 2016.the patients were seen in eye OPD by ophthalmologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…However, both these studies did not consider conjunctivitis as they had focused only on the eye diseases causing visual impairment. The percentage of RE cases in our hospital based study was 21% of the enrolled cases, which is lower than other published papers reporting the prevalence of RE to be ranging from 26% to 40.8% [1,10,22]. In the current study, RE was more common among females with more prevalence of hyperopia, which is in line with the other studies [23,24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, both these studies did not consider conjunctivitis as they had focused only on the eye diseases causing visual impairment. The percentage of RE cases in our hospital based study was 21% of the enrolled cases, which is lower than other published papers reporting the prevalence of RE to be ranging from 26% to 40.8% [1,10,22]. In the current study, RE was more common among females with more prevalence of hyperopia, which is in line with the other studies [23,24].…”
Section: Discussionsupporting
confidence: 82%
“…The PED also varies among children, adults and elderly people. Hospital based studies have been conducted in some countries to highlight the pattern of eye diseases [1][2][3][4]. While some studies have focused on the pattern of ocular morbidity in children [5][6][7] other researchers have studied the PED in elderly age groups [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…After approval by the institutional ethics review committee, the sample size was calculated using a formula in line with literature 13 . As no recent or old local epidemiological study was found related to the incidence of acquired NLD obstruction, the prevalence was taken as 3.1%, which was the average of two studies reporting adult chronic dacryocystitis (0.79%) 14, and paediatric NLD obstruction (5.8%) 15 . Confidence interval (CI) was kept at 95%, alpha value at 0.05, standard normal variate at 1.96, and absolute precision was at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The high prevalence of refractive errors and cataracts shows that hospital still requires an improved infrastructure with spectacle provision to the patients. 16 A study was conducted to know the prevalence of ocular morbidity in school going children of…”
mentioning
confidence: 99%